A comprehensive review of Microfluidic approaches in cell-free synthetic biology - Baranwal, Amogh Kumar; Maerkl, Sebastian J. (Frontiers in Synthetic Biology, 2024)
Cell-free synthetic biology has gained increasing popularity owing to its ability to elucidate biological functions in isolation from intricate cellular environments and the capacity to build increasingly complex biochemical systems in vitro. But cell-free transcription—translation systems are often only available in small volumes which has been a major challenge in the field. Microfluidic technologies helped address this challenge by enabling miniaturization and implementation of robust multi-step workflows. In this review, we highlight microfluidic technologies which have been applied to cell-free applications and discuss various ways in which they have advanced the boundaries of cell-free synthetic biology.